Historical spatial reconstruction of a spawning‐aggregation fishery. Issue 6 (10th August 2017) - Buckley, Sarah M.; Thurstan, Ruth H.; Tobin, Andrew; Pandolfi, John M.
Abstract: Aggregations of individual animals that form for breeding purposes are a critical ecological process for many species, yet these aggregations are inherently vulnerable to exploitation. Studies of the decline of exploited populations that form breeding aggregations tend to focus on catch rate and thus often overlook reductions in geographic range. We tested the hypothesis that catch rate and site occupancy of exploited fish‐spawning aggregations (FSAs) decline in synchrony over time. We used the Spanish mackerel (Scomberomorus commerson) spawning‐aggregation fishery in the Great Barrier Reef as a case study. Data were compiled from historical newspaper archives, fisher knowledge, and contemporary fishery logbooks to reconstruct catch rates and exploitation trends from the inception of the fishery. Our fine‐scale analysis of catch and effort data spanned 103 years (1911–2013) and revealed a spatial expansion of fishing effort. Effort shifted offshore at a rate of 9.4 nm/decade, and 2.9 newly targeted FSAs were reported/decade. Spatial expansion of effort masked the sequential exploitation, commercial extinction, and loss of 70% of exploited FSAs. After standardizing for improvements in technological innovations, average catch rates declined by 90.5% from 1934 to 2011 (from 119.4 to 11.41 fish/vessel/trip). Mean catch rate of Spanish mackerel and occupancy of exploited mackerel FSAs were not significantly related. Our study revealed a special kind of shifting spatial baseline in which a contraction in exploited FSAs occurred undetected. Knowledge of temporally and spatially explicit information on FSAs can be relevant for the conservation and management of FSA species.